2011
DOI: 10.1007/s13361-011-0266-x
|View full text |Cite
|
Sign up to set email alerts
|

Probing Protein Surface with a Solvent Mimetic Carbene Coupled to Detection by Mass Spectrometry

Abstract: Much knowledge into protein folding, ligand binding, and complex formation can be derived from the examination of the nature and size of the accessible surface area (SASA) of the polypeptide chain, a key parameter in protein science not directly measurable in an experimental fashion. To this end, an ideal chemical approach should aim at exerting solvent mimicry and achieving minimal selectivity to probe the protein surface regardless of its chemical nature. The choice of the photoreagent diazirine to fulfill t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…A recently developed nonspecific covalent label is the use of carbenes that are photoreactive. 104 The addition of diazirines to the solution followed by irradiation at near-ultraviolet wavelength (310–350 nm), which is outside the absorbance window of amino acids, results in the formation of reactive carbenes. Once formed, the carbene has an approximate lifetime of a few ns, which allows fast sampling of a protein state.…”
Section: Covalent Labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently developed nonspecific covalent label is the use of carbenes that are photoreactive. 104 The addition of diazirines to the solution followed by irradiation at near-ultraviolet wavelength (310–350 nm), which is outside the absorbance window of amino acids, results in the formation of reactive carbenes. Once formed, the carbene has an approximate lifetime of a few ns, which allows fast sampling of a protein state.…”
Section: Covalent Labelingmentioning
confidence: 99%
“…The advantage of using a specific covalent label is that it reduces the complexity of data analysis. A recently developed nonspecific covalent label is the use of carbenes that are photoreactive . The addition of diazirines to the solution followed by irradiation at near-ultraviolet wavelength (310–350 nm), which is outside the absorbance window of amino acids, results in the formation of reactive carbenes.…”
Section: Covalent Labelingmentioning
confidence: 99%
“…Various labels can be utilized, including amino acid side chain-specific labeling reagents such as iodoacetamide (cysteines), N-bromosuccinimide (tryptophan), diethylpyrocarbonate (carboxyl acids), and S,S 1 -dimethylthiobutanoy lhdroxysuccinimide (lysines). [14][15][16][17] Structural information from these reagents may not be as comprehensive due to their inherent specificities.…”
Section: Structural Analysis Of a Therapeutic Monoclonal Antibody Dimmentioning
confidence: 99%
“…Delfino et al [17, 18] used 3 H-methylene so that its concentration in solution can be monitored, and they demonstrated that methylene reactivity is a monitor of protein conformational transitions and protein interactions. In their later work, Delfino et al [19, 20] used mass spectrometry as the analytical method to achieve accurate detection of footprinting products and map solvent accessibility of proteins. Gas bubbling devices were used in their experiments to mix methylene gas with protein solutions, and reactions were initiated by a halogen/Hg lamp or a Hg/Xe arc source.…”
Section: Introductionmentioning
confidence: 99%